Understanding hypnosis : theory, scope and potential - Barrios, Alfred A. (Nova Science Publishers, 2009)
"The book presents a comprehensive theory of hypnosis one that encompasses and may even surpass all previous theories. It is a rational scientific explanation of hypnosis that explains the hypnotic induction process as well as hypnotic and post-hypnotic phenomena in terms of principles if conditioning and inhibition."--Jacket